2021
DOI: 10.1177/11206721211023317
|View full text |Cite
|
Sign up to set email alerts
|

Management of cataracts secondary to intravitreal chemotherapy injections for retinoblastoma seeding

Abstract: Purpose: To report our experience in the management of cataracts presumably due to intravitreal chemotherapy administration in eyes with vitreous disease associated with retinoblastoma. Methods: This retrospective study consisted of a cohort of five eyes of five retinoblastoma patients who developed cataracts secondary to intravitreal chemotherapy administration and who then underwent cataract surgery. All patients underwent lensectomy and anterior vitrectomy with/without intraocular lens implantation via clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Intraocular surgeries in eyes with Rb remains strongly associated with challenges and the major concerns are extraocular spread and distant metastases [ 19 , 20 ]. In patients with retinoblastoma, it is commonly accepted that intraocular surgeries (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular surgeries in eyes with Rb remains strongly associated with challenges and the major concerns are extraocular spread and distant metastases [ 19 , 20 ]. In patients with retinoblastoma, it is commonly accepted that intraocular surgeries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with retinoblastoma, it is commonly accepted that intraocular surgeries (e.g. cataract surgery) should be delayed until complete tumor control is achieved, but there is controversy regarding the best time for doing surgery [ 19 20 ]. It is recommended to postpone these surgeries between 18 and 24 months after complete tumor control [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a reported series of 29 eyes with treated Rb undergoing cataract surgery by Kaliki et al ,1 only one eye had IVitC-induced cataract. More recently, Koç et al 11 have reported a series of five eyes of five patients with Rb who developed cataracts secondary to IVitC and subsequently underwent clear corneal lensectomy and anterior vitrectomy with or without an IOL implant. These patients also received intravitreal melphalan or topotecan intraoperatively as prophylaxis against possible tumour dissemination and subsequently received repeat monthly injections as required.…”
Section: Discussionmentioning
confidence: 99%